PEMBERDAYAAN ETOS KERJA MASYARAKAT DALAM PERSPEKTIF AL-QUR’AN - Ridwan, Ridwan; Bukhari, Bukhari (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
Working in the perspective of the Holy Quran is the duty of every Muslim. Work is not just to meet the necessities of life, but is a worship to glorify and increase its degree. Every work done because of Allah is the same as doing Jihad fῑ Sabῑlillah. Jihad in work requires motivation, discipline and a work ethic based on the Holy Quran and Hadith. The work ethic in Islam will be faced with three responsibilities, namely towards Allah, himself, and others as a manifestation of his faith. A person's work success is determined by a high work ethic rooted in him. The motivation and work ethic in Islam is that which emphasizes the values of the Qur'an. It is an obligation for humans as beings who have many needs and interests in life to work to meet all their needs. A Muslim must balance between the needs of the world and the hereafter. A Muslim is not only oriented to the interests of the afterlife, but also must think about his worldly interests, therefore it is necessary to empower the work ethic of society.